Optimization of Conditions for the Synthesis and Oxidation of 5,8-Dimethoxy-2-methyl-3,4-dihydroisoquinolin-1(2H)-one into Novel 2-Methylisoquinoline-1,5,8(2H)-trione - Basharat Ali; Faiz Ahmed; Nusrat Shafiq; Muhammad Nasrula (Orbital: The Electronic Journal of Chemistry, 2020)
Due to stability issue of isoquinolone’s their N-methylation is a challenging task, achieved the synthesis of N-methylated 2-methylisoquinoline-1,5,8(2H)-trione using readily available precursor 2-(2,5-dimethoxyphenyl)ethanamine via multistep strategy, finally oxidation of 5,8-dimethoxy-2-methyl-3,4-dihydroisoquinolin-1(2H)-one with ceric ammonium nitrate (CAN) lead to target isoquinolone in good yield, further oxidation conditions in final step were optimized using different catalyst ratio, reaction time and temperature conditions.DOI: http://dx.doi.org/10.17807/orbital.v12i1.143